Solid-state lithium battery cell and preparation method thereof, and battery
By introducing a carbonized layer into a solid-state lithium battery and penetrating the conductive dielectric, the problem of high contact impedance between the solid-state electrolyte and the negative electrode is solved, the performance and safety of the battery are improved, and the internal resistance of the battery is achieved and the energy is higher. density.
Patent Information
- Application Number
- CN202010975508.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-09-16
AI Technical Summary
The contact impedance between the solid electrolyte and the positive electrode and the negative electrode in solid-state lithium batteries is too large, resulting in limited battery performance.
A carbonized layer is introduced into a solid-state lithium battery and a conductive dielectric penetrates therein to ensure that the conductive dielectric is connected to the negative electrode sheet and reduce the interface impedance between the carbonized layer and the negative electrode sheet.
By increasing the conductive contact area between the carbonized layer and the negative electrode sheet, the interface impedance between the solid electrolyte and the negative electrode sheet is reduced, the discharge capacity and efficiency of the battery are improved, and the internal resistance of the battery is reduced.
Smart Images

Figure CN114267883B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a solid-state lithium battery cell and a preparation method thereof, and a battery. Background Art
[0002] With the increasing popularity of new energy vehicles, the requirements for the use of power batteries in new energy vehicles have become increasingly higher. In the past three decades, compared with traditional lead-acid, nickel-metal hydride and other secondary batteries, lithium-ion batteries with high energy density, high output voltage and environmental friendliness have been rapidly developed and widely used. In the structure of lithium-ion batteries, electrolyte is an indispensable and important component of lithium-ion batteries, and is a necessary condition for lithium-ion batteries to obtain advantages such as high voltage and high cycle performance. Lithium-ion batteries usually use organic solvents as electrolytes, and these organic solvents are extremely flammable. Once the battery generates high temperature or sparks due to internal short circuit, the electrolyte will be ignited in an instant and cause the entire battery to explode. Converting flammable liquid electrolytes into solid electrolytes can reduce safety risks caused by flammability, and at the same time, better performance can be obtained. However, the large contact impedance between the solid electrolyte and the positive and negative electrodes has always been a major problem hindering the development of solid-state batteries. Summary of the invention
[0003] The content of the present application aims to solve at least one of the technical problems existing in the prior art. To this end, in the first aspect of the present application, a solid-state lithium battery cell is provided, the solid-state lithium battery cell comprising a positive electrode sheet, a solid electrolyte, a carbonized layer and a negative electrode sheet stacked in sequence, a conductive medium is infiltrated into the carbonized layer, the length of the conductive medium in the thickness direction of the carbonized layer is less than the sum of the thickness of the carbonized layer and the thickness of the solid electrolyte, and the conductive medium is connected to the negative electrode sheet.
[0004] In a second aspect of the present application, a method for preparing a solid-state lithium battery cell is provided, wherein the method for preparing the solid-state lithium battery cell comprises:
[0005] preparing a positive electrode sheet;
[0006] placing a solid electrolyte precursor on the positive electrode sheet;
[0007] A molten conductive medium precursor is coated on the surface of the solid electrolyte precursor away from the positive electrode sheet. The molten conductive medium precursor cools and releases heat so that the surface of the solid electrolyte precursor away from the positive electrode sheet is heated and carbonized to form a carbonized layer. The remaining part of the solid electrolyte precursor is cooled to form a solid electrolyte. At least part of the molten conductive medium precursor penetrates into the carbonized layer to form a conductive medium, and a negative electrode sheet is formed on the surface of the carbonized layer away from the solid electrolyte.
[0008] In a third aspect of the present application, a battery is provided, comprising a housing and the solid-state lithium battery cell as described above located in the housing.
[0009] Beneficial effects of the present invention: The carbonized layer in the solid-state lithium battery cell provided by the present invention is infiltrated with a conductive medium, which increases the conductive contact area between the carbonized layer and the negative electrode sheet, thereby reducing the interface impedance between the solid electrolyte and the negative electrode sheet, thereby reducing the internal resistance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0011] Figure 1 A schematic diagram of the structure of a solid-state lithium battery cell provided by an embodiment of the present invention;
[0012] Figure 2 A SEM structural diagram of the “blended” interface of metal lithium / in-situ carbonized layer / solid electrolyte layer in a solid-state lithium battery cell provided in one embodiment of the present invention;
[0013] Figure 3 This is a distribution diagram of XPS results of the carbonized layer in a solid-state lithium battery cell provided in one embodiment of the present invention;
[0014] Figure 4 A flow chart of a method for preparing a solid-state lithium battery cell provided by one embodiment of the present invention;
[0015] Figure 5 Capacity retention rate distribution curves of batteries prepared in Example 1, Example 3, Example 4 and Comparative Example 1 under different charge and discharge cycle numbers provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0016] The following is a preferred embodiment of the present invention. It should be noted that a person skilled in the art may make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
[0017] See also Figure 1 and Figure 2, an embodiment of the present invention provides a solid-state lithium battery cell 10, the solid-state lithium battery cell 10 comprises a positive electrode sheet 100, a solid electrolyte 200, a carbonized layer 300 and a negative electrode sheet 400 which are stacked in sequence. A conductive medium 410 is infiltrated into the carbonized layer 300, the length of the conductive medium 410 in the thickness direction of the carbonized layer 300 is less than the sum of the thickness of the carbonized layer 300 and the thickness of the solid electrolyte 200, and the conductive medium 410 is connected to the negative electrode sheet 400. Among them, the conductive medium 410 refers to a medium with conductive properties, which can be metal lithium, metal sodium, metal aluminum or metal magnesium. The negative electrode sheet 400 can be a metal negative electrode sheet or a non-metallic negative electrode sheet, the metal negative electrode sheet includes a metal lithium sheet, a metal sodium sheet or a metal aluminum sheet, and the non-metallic negative electrode sheet can be a graphite negative electrode sheet, a soft carbon negative electrode sheet or a silicon-containing negative electrode sheet. The conductive medium 410 and the negative electrode sheet 400 can be formed simultaneously or in steps. The conductive medium 410 is set to be infiltrated in the carbonized layer 300, and the conductive medium 410 is electrically connected to the negative electrode sheet 400, which increases the contact area of the electrical connection between the carbonized layer 300 and the negative electrode sheet 400, thereby effectively reducing the interface impedance between the solid electrolyte 200 and the negative electrode sheet 400. In addition, the length of the conductive medium 410 in the thickness direction of the carbonized layer 300 is set to be less than the sum of the thickness of the carbonized layer 300 and the thickness of the solid electrolyte 200, which can prevent the conductive medium 410 from passing through the solid electrolyte 200 to connect with the positive electrode sheet 100, thereby effectively preventing the positive electrode sheet 100 and the negative electrode sheet 400 from being electrically connected and causing a short circuit.
[0018] The carbonized layer 300 in the solid-state lithium battery cell provided by the present invention is infiltrated with a conductive medium 410, which increases the conductive contact area between the carbonized layer 300 and the negative electrode sheet 400, thereby reducing the interface impedance between the solid electrolyte 200 and the negative electrode sheet 400, and further reducing the internal resistance of the battery.
[0019] In the present application, the conductive medium 410 is preferably metallic lithium, and the negative electrode sheet 400 is preferably metallic lithium. The conductive medium 410 and the negative electrode sheet 400 are both lithium metal, which can reduce the interface impedance between the two. When the conductive medium 410 and the negative electrode sheet 400 are both lithium metal, the two can be formed at the same time.
[0020] In the present application, the carbonized layer 300 is formed by carbonizing the surface of the solid electrolyte precursor facing the negative electrode sheet 400 by heat, and the raw material of the carbonized layer 300 before carbonization is the same as the raw material of the solid electrolyte 200 before solidification and polymerization. The solid electrolyte precursor is used to form the solid electrolyte 200, which means that the solid electrolyte 200 is an intermediate product before solidification and polymerization. In the present application, the side of the carbonized layer 300 adjacent to the solid electrolyte 200 is mutually infiltrated and blended with the solid electrolyte 200, and there is no obvious interface between the two. The conductive medium 410 penetrates into the carbonized layer 300 and interweaves with the carbonized layer 300, which can increase the contact area between the carbonized layer 300 and the negative electrode sheet 400, so as to increase the ion transfer area, and further reduce the interface impedance between the solid electrolyte 200 and the negative electrode sheet 400. Among them, the side where the carbonized layer 300 and the conductive medium 410 are interwoven is uneven (such as Figure 2 shown).
[0021] In some embodiments, one end of the conductive medium 410 away from the negative electrode sheet 400 is spaced apart from the positive electrode sheet 100 , thereby preventing the negative electrode sheet 400 from being electrically connected to the positive electrode sheet 100 .
[0022] In some embodiments, the length of the conductive medium 410 along the thickness direction of the carbonized layer 300 is at most the same as the thickness of the carbonized layer 300, or the end of the conductive medium 410 away from the negative electrode sheet 400 is located in the carbonized layer 300. This allows the conductive medium 410 to be spaced from the positive electrode sheet 100 to avoid electrical connection between the two. In other embodiments, the conductive medium 410 passes through the carbonized layer 200 and penetrates into the solid electrolyte 200, but does not pass through the solid electrolyte 200.
[0023] In a further embodiment, the thickness of the carbonized layer 300 is 5 μm-10 μm. In the present application, the carbonized layer 300 is formed by coating the molten metal lithium on the surface of the solid electrolyte 200 so that the surface is carbonized by heat. When the thickness of the carbonized layer 300 is within the above range, the interface impedance can be effectively reduced while the conductive medium 410 can be coated in the carbonized layer 300 to avoid the end of the conductive medium 410 being electrically connected to the positive electrode sheet 100.
[0024] In a further embodiment, the length of the conductive medium 410 in the thickness direction of the carbonized layer 200 is 1 μm-10 μm. When the conductive medium 410 is within the above length range, the interface impedance between the solid electrolyte 200 and the negative electrode sheet 400 is low, and when applied to the prepared battery, the internal resistance of the battery can be reduced.
[0025] In a further embodiment, the conductivity of the carbonized layer 300 gradually decreases from the direction close to the negative electrode sheet 400 to the direction away from the negative electrode sheet 400. On the one hand, the carbonized layer 300 is formed by carbonizing the surface of the solid electrolyte precursor facing the negative electrode sheet 400 by heat, so the raw material of the carbonized layer 300 contains organic components, and the organic components are decomposed from macromolecules into small molecules or form carbon single substance during the heat carbonization process. The greater the degree of carbonization, the smaller the small molecules formed or the more carbon single substance formed, and the smaller the small molecules or the more carbon single substance formed, the stronger the conductivity. In this embodiment, when the conductive medium 410 and the negative electrode sheet 400 are formed by coating molten metal lithium on a solid electrolyte precursor, the solid electrolyte precursor portion corresponding to the carbonized layer 300 and in direct contact with the molten metal lithium is carbonized to the highest degree, and the solid electrolyte precursor portion farther away from the negative electrode sheet 400 is carbonized to a lower degree, so the conductivity of the carbonized layer 300 gradually decreases from the direction close to the negative electrode sheet 400 to the direction away from the negative electrode sheet 400. On the other hand, the small molecules or carbon single substance formed by the portion of the carbonized layer 300 close to the negative electrode sheet 400 are more conducive to the extension of the conductive medium 410 therein than the macromolecule portion far away from the negative electrode sheet 400, further improving the interface fusion degree between the carbonized layer 300 and the negative electrode sheet 400; when the molten metal lithium is coated on the solid electrolyte precursor and infiltrated into the carbonized layer 300, the metal lithium infiltrated into the carbonized layer 300 farther away from the negative electrode sheet 400 is less, and the less metal lithium, the worse the conductivity.
[0026] See also Figure 3 In a further embodiment, the carbonized layer 300 is also doped with nitrogen. The nitrogen includes four forms of nitrogen doping, and the four forms of nitrogen doping are pyridine nitrogen, pyrrole nitrogen, graphite nitrogen and oxidized nitrogen. Nitrogen has a strong electronegativity and is easy to complex with the conductive medium 410, for example, it is easy to complex with metallic lithium. After the four forms of nitrogen are complexed with metallic lithium, the metallic lithium can be further wrapped in the carbonized layer 300, thereby making the carbonized layer 300 more integrated with the metallic lithium. Therefore, the carbonized layer 300 doped with nitrogen and the conductive medium 410 are mutually infiltrated, blended and integrated, which further illustrates that the interface contact area between the carbonized layer 300 and the negative electrode sheet 400 of the present application is large, and the interface impedance can be effectively reduced.
[0027] Please continue reading Figure 1In a further embodiment, the positive electrode sheet 100 includes a positive electrode collector 110 and a positive electrode material layer 120 disposed on the surface of the positive electrode collector 110, and the positive electrode material layer 120 includes a spinel positive electrode material. The current spinel positive electrode material is mainly used in batteries with liquid electrolytes, but the electrolyte is very easy to react with the spinel positive electrode material in high-voltage long cycles, causing the manganese element in the positive electrode material to dissolve and migrate to the negative electrode, resulting in irreversible loss of manganese elements, and problems such as spinel crystal structure reformation, which in turn causes the overall voltage and capacity of the battery to decay rapidly, and the cycle performance is poor. In this application, combining the spinel positive electrode material with a solid electrolyte can effectively avoid the above problems, and can effectively give play to the high energy density advantage of the spinel positive electrode material. In one embodiment, a high operating voltage and high energy density greater than 4.6V can be achieved by matching the spinel positive electrode material with a solid electrolyte and a lithium metal layer negative electrode material. This solid-state lithium metal battery has high operating voltage, high energy density, low impedance and high safety, and has good cycle stability, which can greatly improve the endurance, power and safety performance of future power vehicles.
[0028] In a further embodiment, the surface of the positive electrode current collector 110 is subjected to stamping, etching or roughening treatment to increase the surface roughness, increase the surface contact area between the positive electrode current collector 110 and the electrode material layer 120 or increase the adhesion between the two.
[0029] In some embodiments, a groove 111 is provided on one side of the positive electrode current collector 110 facing the solid electrolyte 200, and a positive electrode material layer 120 is provided on one side of the positive electrode current collector 110 facing the solid electrolyte 200 and in the groove 111. The positive electrode material layer 120 may be coated only on the surface of the groove 111, or may be filled in the groove 111. In this embodiment, the positive electrode material layer 120 is filled in the groove 111.
[0030] In a further embodiment, the portion of the positive electrode material layer 120 close to the solid electrolyte 200 is also infiltrated with solid electrolyte material.
[0031] Specifically, the positive electrode material layer 120 includes positive electrode material particles 121, and there are gaps 122 between the positive electrode material particles 121. The solid electrolyte 200 includes electrolyte branches 210 facing the positive electrode sheet 100, and the electrolyte branches 210 penetrate into the gaps 122 between the positive electrode material particles 121. In the present application, it is preferred to coat the liquid solid electrolyte precursor in the positive electrode material layer 120, and the liquid solid electrolyte precursor will penetrate into the gaps 122 between the positive electrode material particles 121. When the solid electrolyte is formed after polymerization and curing under heat, the liquid solid electrolyte precursor that penetrates into the gaps 122 between the positive electrode material particles 121 is polymerized and cured into the electrolyte branches 210. The shape of the electrolyte branches 210 matches the shape of the gaps 122 between the positive electrode material particles 121. In this embodiment, the electrolyte branches 210 and the positive electrode material particles 121 are intermingled and infiltrated with each other, which can effectively increase the interface contact area between the positive electrode material layer 120 and the solid electrolyte 200 and reduce the interface impedance.
[0032] See also Figure 4 An embodiment of the present invention further provides a method for preparing a solid-state lithium battery cell 10, wherein the method for preparing the solid-state lithium battery cell 10 comprises steps S100, S200 and S300. The detailed steps are as follows.
[0033] Step S100, preparing a positive electrode sheet 100.
[0034] Step S200, a solid electrolyte precursor is disposed on the positive electrode sheet 100. In the present application, the solid electrolyte precursor is a liquid solid electrolyte precursor or a semi-solid solid electrolyte precursor, and the solid electrolyte precursor refers to a monomer in its raw material that has not undergone polymerization reaction or has not been completely polymerized. When the solid electrolyte precursor is a liquid solid electrolyte precursor, the liquid solid electrolyte precursor can be infiltrated on the positive electrode sheet 100, and when the solid electrolyte precursor is a semi-solid solid electrolyte precursor, the semi-solid solid electrolyte precursor can be squeezed on the positive electrode sheet 100 by pressure.
[0035] Step S300, coating the molten conductive medium precursor on the surface of the solid electrolyte precursor away from the positive electrode sheet 100, the molten conductive medium precursor cools and releases heat so that the surface of the solid electrolyte precursor away from the positive electrode sheet 100 is heated and carbonized to form a carbonized layer 300, the rest of the solid electrolyte precursor is cooled to form a solid electrolyte 200, at least part of the molten conductive medium precursor penetrates into the carbonized layer 300 to form a conductive medium 410, and the negative electrode sheet 400 is formed on the surface of the carbonized layer 300 away from the solid electrolyte 200. Among them, the conductive medium 410 refers to a medium with conductive properties, which can be metal lithium, metal aluminum, metal magnesium, etc. The negative electrode sheet 400 can be a metal negative electrode sheet or a non-metallic negative electrode sheet, the metal negative electrode sheet includes a metal lithium sheet or a metal aluminum sheet, etc., and the non-metallic negative electrode sheet can be a graphite negative electrode sheet, a soft carbon negative electrode sheet, or a silicon-containing negative electrode sheet. In this embodiment, the conductive medium 410 is metal lithium, and the negative electrode sheet 400 is a metal lithium sheet.
[0036] In the step S100, in a further embodiment, the method for preparing the positive electrode sheet 100 includes steps S110 and S120. The detailed steps are as follows.
[0037] Step S110, providing a positive electrode current collector 110, on which grooves 111 are formed. Specifically, the grooves 111 arranged evenly spaced can be formed by stamping. The shape of the grooves 111 is not limited in the present application, and in some embodiments, can be arc-shaped, semicircular, square or rectangular, and the shapes of the plurality of grooves 111 can be the same or different, and the intervals between the plurality of grooves 111 can be equal or unequal.
[0038] In step S120 , a positive electrode material is coated on the surface of the positive electrode current collector 110 adjacent to the groove 111 and in the groove, and then dried to form the positive electrode sheet 100 .
[0039] The positive electrode material includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material, the binder and the conductive agent are mixed and dispersed in an N-methylpyrrolidone solvent in a mass ratio of (84-98): (1-8): (1-8), and then sieved, coated, baked, rolled and die-cut to form a positive electrode sheet, wherein the positive electrode active material is a single crystal LiNi 0.5-x Mn 1.5 M x O4, 0≤x≤0.2, the M is selected from at least one of Nb, Fe, Zn, Cu, Co, Ce or La, the D50 particle size of the positive electrode active material single crystal particles is 9-11 μm, and the compaction density is 2.5-3.0 g·cm -3; The binder is one or both of polyvinylidene fluoride and sodium carboxymethyl cellulose; The conductive agent is one or more of carbon black, carbon nanotubes, graphene, and acetylene black. Wherein, the positive electrode active material is a spinel positive electrode material or a layered positive electrode material. In this embodiment, the spinel positive electrode material is preferred, and the spinel positive electrode material has a higher capacity density and a lower cost.
[0040] In the above step S200, the solid electrolyte precursor includes an olefin monomer, a cross-linking agent, a thermal initiator and a lithium salt, and the mass ratio of olefin monomer: cross-linking agent: thermal initiator: lithium salt is 100: (0.05-0.25): (0.05-0.25): (8-12).
[0041] In a further embodiment, the olefin monomer includes one or more of methyl methacrylate, vinyl alcohol, and acrylonitrile. The olefin monomer is polymerized under the action of a thermal initiator to form a polymer. In other embodiments, the olefin monomer may also be other types of olefins.
[0042] In a further embodiment, the cross-linking agent includes one or both of styrene and ethylene glycol dimethyl acrylate. The cross-linking agent is used to solidify the generated polymer and enhance the strength of the solid electrolyte.
[0043] In a further embodiment, the thermal initiator includes one or both of azobisisobutyronitrile and diphenylmethane peroxide. The thermal initiator is used to initiate polymerization of olefin monomers. The azobisisobutyronitrile or diphenylmethane peroxide contains nitrogen, so that the formed carbonized layer 300 is doped with nitrogen, thereby allowing the conductive medium 410 and the carbonized layer 300 to interpenetrate and blend with each other.
[0044] In a further embodiment, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium difluorophosphate. The lithium salt is used to provide lithium ions for the solid electrolyte.
[0045] In the above step S200, the solid electrolyte precursor also includes an organic solvent. After dissolving and dispersing the olefin monomer, the cross-linking agent, the thermal initiator and the lithium salt in the organic solvent, the solid electrolyte precursor is coated on the positive electrode sheet 100. The amount of the organic solvent can be set according to the amount of the solid electrolyte precursor. For example, in some embodiments, the organic solvent is 1.5-3 times the total mass of the olefin monomer, the cross-linking agent, the thermal initiator and the lithium salt. In some embodiments, the thickness of the solid electrolyte 200 can be set by the viscosity of the solid electrolyte precursor and the temperature of the molten metal lithium. For example, when a thinner solid electrolyte is required, the viscosity of the solid electrolyte precursor can be reduced, but the minimum viscosity of the solid electrolyte precursor must be sufficient to support the molten metal lithium coated on its surface, so that the conductive medium 410 cannot pass through the solid electrolyte 200 and be electrically connected to the positive electrode sheet 100; when a thicker solid electrolyte is required, the viscosity of the solid electrolyte precursor can be increased. In the present application, the thickness of the solid electrolyte 200 can be set as thin as possible while ensuring that the conductive medium 410 is not electrically connected to the positive electrode sheet 100. The thinner the solid electrolyte 200, the more conducive it is to the transmission of lithium ions between the positive electrode sheet 100 and the negative electrode sheet 400, thereby improving the conductivity.
[0046] In a further embodiment, the solid electrolyte precursor further comprises ceramic powder, and the mass ratio of the olefin monomer to the ceramic powder is 100:(0.05-0.25). The ceramic powder is used to enhance the structural strength of the solid electrolyte. In this embodiment, the ceramic powder is preferably Li 1.3 Al 0.3 Ti 1.7 (PO4)3 can, on the one hand, increase the structural strength of the solid electrolyte 200, and on the other hand, provide lithium ions, which is beneficial to improving the conductivity of the solid electrolyte 200.
[0047] In the above step S200, the solid electrolyte precursor is preferably spin-coated and soaked on the positive electrode sheet 100 to increase the permeability of the solid electrolyte precursor in the positive electrode material layer 120 in the positive electrode sheet 100, which can improve the degree of fusion between the solid electrolyte branch 210 and the positive electrode material layer 120, thereby increasing the contact area between the solid electrolyte 200 and the positive electrode material layer 120, reducing the interface impedance, and further reducing the internal resistance of the battery.
[0048] In the above step S300, the conductive medium precursor is metallic lithium; the at least partially molten conductive medium precursor infiltrates into the carbonized layer 300, and forms the negative electrode sheet 400 on the surface of the carbonized layer 300 away from the solid electrolyte 200, including: partially molten metallic lithium infiltrates into the carbonized layer 300, and another partially molten metal layer cools on the surface of the carbonized layer 300 away from the solid electrolyte 200 to form a metallic lithium layer, and the metallic lithium layer is the negative electrode sheet 400. The molten metallic lithium can be obtained by polishing at least one surface of a lithium sheet, a lithium belt, a lithium wire, or a lithium particle, cutting it into a negative electrode sheet of a suitable size, and then melting it. The molten metallic lithium is coated on the surface of the solid electrolyte precursor away from the positive electrode sheet 100 by uniform drip coating, and the molten metallic lithium cools and releases heat to form a carbonized layer 300 of part of the solid electrolyte precursor. The carbonized layer 300 described in the present application is formed by direct carbonization of a solid electrolyte precursor, that is, before carbonization, the solid electrolyte precursor is in a liquid or semi-solid state. When molten metallic lithium is dripped onto the surface of the liquid or semi-solid solid electrolyte precursor, a portion of the metallic lithium will penetrate into the solid electrolyte precursor. During the carbonization process, the portion of the solid electrolyte precursor in contact with or adjacent to the molten metallic lithium will be heated to induce polymerization and carbonize to form a carbonized layer. Part of the metallic lithium will penetrate into the solid electrolyte precursor, and another portion of the molten metallic lithium will cool on the surface of the carbonized layer 300 away from the solid electrolyte 200 to form a metallic lithium layer, while the portion of the solid electrolyte precursor away from the molten metallic lithium undergoes a polymerization reaction under the initiation of a thermal initiator to form a solid electrolyte. In the present application, the solid electrolyte precursor is heated to induce polymerization and carbonization at the same time.
[0049] In some embodiments, the conductive medium 410 and the negative electrode sheet 400 are formed separately, and the molten metal lithium can be dripped onto the surface of the solid electrolyte precursor. After the metal lithium is cooled, the negative electrode sheet 400 is attached to the surface of the carbonized layer 200 .
[0050] In a further embodiment, the thickness of the carbonized layer 300 is 5-10 μm. The thickness of the negative electrode sheet 400 is 10-50 μm, wherein the thickness of the negative electrode sheet 400 does not include the length of the conductive medium 410 extending into the carbonized layer 300. The thickness of the solid electrolyte 200 is 10-50 μm, wherein the thickness of the solid electrolyte 200 does not include the length of the solid electrolyte branch 210 infiltrated into the positive electrode material layer 120.
[0051] In a further embodiment, the carbonized layer 300 is also doped with nitrogen. The nitrogen includes four forms of nitrogen doping, and the four forms of nitrogen doping are pyridine nitrogen, pyrrole nitrogen, graphite nitrogen and oxidized nitrogen. Nitrogen has a strong electronegativity and is easy to complex with the conductive medium 410, for example, it is easy to complex with metallic lithium. After the four forms of nitrogen are complexed with metallic lithium, the metallic lithium can be further wrapped in the carbonized layer 300, thereby making the carbonized layer 300 and the metallic lithium more fused. Therefore, the carbonized layer 300 containing nitrogen doping and the conductive medium 410 are mutually infiltrated and integrated, further illustrating that the interface contact area between the carbonized layer 300 and the negative electrode sheet 400 of the present application is large, and the interface impedance can be effectively reduced, greatly improving the transmission efficiency of electrons and ions, while reducing the electronic and ion impedance. In the present application, the nitrogen element in the four forms of nitrogen comes from a thermal initiator, the nitrogen ion has a high electronegativity, and the four forms of nitrogen doping can promote lithium ion transmission.
[0052] In one embodiment, when the solid electrolyte precursor is semi-solid, the semi-solid solid electrolyte precursor is quickly made into a battery together with the positive electrode sheet and the molten lithium metal negative electrode, and then fixed by a clamp, and heated in situ under pressurized state to induce the semi-solid solid electrolyte precursor to form a polymer electrolyte that penetrates the gaps between the positive and negative electrodes, and simultaneously forms a metal lithium layer, a solid electrolyte and a carbonized layer, thereby maximizing the interface contact area between the solid electrolyte and the metal lithium layer and the positive electrode sheet, greatly improving the interface ion diffusion and exchange efficiency.
[0053] In some embodiments, when the molten conductive medium precursor infiltrates the solid electrolyte precursor to form the conductive medium 410 , pressure may be applied to the conductive medium 410 to allow the conductive medium 410 to penetrate through the carbonized layer 300 and penetrate into the solid electrolyte 200 , but not through the solid electrolyte 200 .
[0054] An embodiment of the present invention further provides a battery, the battery comprising a housing and a solid-state lithium battery cell as described in any of the above embodiments located in the housing. The carbonized layer 300 in the solid-state lithium battery cell has a conductive medium 410 inside, which increases the contact area between the carbonized layer 300 and the negative electrode sheet 400, thereby reducing the interface impedance between the solid electrolyte 200 and the negative electrode sheet 400, increasing the discharge capacity and discharge efficiency of the solid-state lithium-ion battery, reducing the internal resistance of the battery, and improving the capacity retention rate of the battery.
[0055] In order to better illustrate the technical solution of the present invention, a description is given below in conjunction with a number of specific embodiments.
[0056] Example 1
[0057] (1) Preparation of positive and negative electrodes
[0058] The positive electrode active material (LiNi 0.5 Mn 1.5 O4), binder (polyvinylidene fluoride), and conductive agent (carbon nanotubes) are mixed and dispersed in N-methylpyrrolidone solvent in a mass ratio of 92:4:4, and then sieved, coated, baked, rolled, and die-cut to form positive electrode sheets. The positive electrode current collector uses carbon-coated aluminum foil with grooves. The metal lithium is polished in an argon-protected glove box, cut into sheets, and melted for later use.
[0059] (2) Solid electrolyte in-situ polymerization to make batteries
[0060] Ethylene carbonate monomer, lithium hexafluorophosphate, thermal initiator (azobisisobutyronitrile), crosslinking agent (styrene), ceramic powder (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) are mixed evenly in a mass ratio of 100:10:1:0.2:0.2 to form a solid electrolyte precursor, and the solid electrolyte precursor is spin-coated on the positive electrode sheet in (1) to form a semi-finished battery, and then molten metal lithium is dripped or spin-coated on the surface of the upper solid electrolyte precursor. The cooling heat of the molten metal lithium causes the surface of the solid electrolyte precursor away from the positive electrode sheet to be heated and carbonized to form a carbonized layer. The other parts of the solid electrolyte precursor adjacent to the carbonized layer are cooled to form a solid electrolyte. After the molten metal lithium is cooled, a metal lithium layer is formed on the surface of the carbonized layer. The molten metal lithium that penetrates into the carbonized layer is cooled to form a lithium conductive medium. The length of the lithium conductive medium that penetrates into the carbonized layer is 5 μm, the thickness of the carbonized layer is 7 μm, and the thickness of the solid electrolyte is 30 μm. It is further aged at 60°C to form a button battery, denoted as S1, wherein the XPS results of the carbonized layer are distributed as follows Figure 3 As shown, from Figure 3 It can be seen that four types of nitrogen are doped in the carbonized layer.
[0061] Example 2
[0062] (1) Preparation of positive and negative electrodes
[0063] The positive electrode active material (LiNi 0.5 Mn 1.5 O4), binder (sodium carboxymethyl cellulose), and conductive agent (carbon black) are mixed and dispersed in N-methylpyrrolidone solvent at a mass ratio of 90:5:5, and then sieved, coated, baked, rolled, and die-cut to form a positive electrode sheet. The electrode sheet uses a grooved carbon-coated aluminum foil. The metal lithium is polished in an argon-protected glove box, cut into sheets, and melted for later use.
[0064] (2) Solid electrolyte in-situ polymerization to make batteries
[0065] Vinyl ethylene carbonate monomer, vinyl alcohol, lithium tetrafluoroborate, thermal initiator (azobisisobutyronitrile), crosslinking agent (styrene), ceramic powder (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) are mixed in a mass ratio of 50:50:10:1:0.2:0.2 to form a solid electrolyte precursor, and the solid electrolyte precursor is spin-coated on the positive electrode sheet in (1) to form a semi-finished battery, and then molten metal lithium is dripped or spin-coated on the surface of the upper solid electrolyte precursor. The cooling heat of the molten metal lithium causes the surface of the solid electrolyte precursor away from the positive electrode sheet to be heated and carbonized to form a carbonized layer, and the other parts of the solid electrolyte precursor adjacent to the carbonized layer are cooled to form a solid electrolyte. After the molten metal lithium is cooled, a metal lithium layer is formed on the surface of the carbonized layer. The molten metal lithium that penetrates into the carbonized layer is cooled to form a lithium conductive medium. The length of the lithium conductive medium that penetrates into the carbonized layer is 5 μm, the thickness of the carbonized layer is 8 μm, and the thickness of the solid electrolyte is 30 μm. The battery is further aged at 60°C to form a button battery, which is denoted as S2. The carbonized layer is analyzed by XPS and is nitrogen-doped.
[0066] Example 3
[0067] The same steps as in Example 1 were used to prepare the pole piece and button cell, except that after a certain amount of molten metallic lithium was dripped on the upper semi-solid solid electrolyte precursor, the battery was quickly made, and the surface was immediately pressurized (10 kPa) and heated to induce polymerization of the solid electrolyte and simultaneous generation of a carbonized layer. The length of the lithium conductive medium that penetrated into the carbonized layer was 7 μm, the thickness of the carbonized layer was 10 μm, and the thickness of the solid electrolyte was 20 μm. The button cell thus prepared was recorded as S3.
[0068] Example 4
[0069] The same steps as in Example 1 were used to prepare the electrode piece and button cell, except that the aluminum foil used was smooth carbon-coated aluminum foil. The button cell was denoted as S4.
[0070] Example 5
[0071] The electrode and button cell were prepared by the same steps as in Example 1, except that when the molten metallic lithium was dripped onto the surface of the solid electrolyte precursor, a smaller amount of molten metallic lithium was used, so that the length of the lithium conductive medium penetrating into the carbonized layer was 0.05 μm. Other conditions were the same as in Example 1, and the prepared button cell was denoted as S5.
[0072] Example 6
[0073] The same steps as in Example 1 were used to prepare the pole piece and button cell, except that the added thermal initiator was a nitrogen-free thermal initiator, methyl ethyl ketone peroxide, and the button cell was recorded as S6.
[0074] Comparative Example 1
[0075] The same steps as in Example 1 were used to prepare the electrode and button cell, except that the solid electrolyte was polymerized first, and then molten metallic lithium was directly dripped on the surface of the cooled solid electrolyte. The button cell was recorded as DS1, and no metallic lithium was infiltrated into the carbonized layer of the prepared battery cell.
[0076] Comparative Example 2
[0077] The same steps as in Example 1 are used to prepare the electrode sheet and button battery, except that when the molten metallic lithium is dripped onto the surface of the solid electrolyte precursor, a larger amount of molten metallic lithium is used, and pressure is applied to both sides of the positive electrode sheet and the negative electrode sheet during the cooling process, so that the lithium conductive medium penetrates through the solid electrolyte and penetrates into the positive electrode sheet. The prepared button battery is recorded as DS2.
[0078] The button batteries prepared in the above Examples 1-6 and Comparative Examples 1-2 were subjected to performance tests, including first cycle charge and discharge performance tests, battery impedance test methods, and cycle performance tests.
[0079] The first cycle charge and discharge performance test method: Charge each experimental button battery S1-S6, DS1-DS2 to 4.95V at a constant current of 0.1C at room temperature, and then discharge it to 3.0V at a constant current of 0.1C. Record the discharge capacity and charge capacity of the battery, and calculate the charge and discharge efficiency (%) = charge capacity / discharge capacity × 100%.
[0080] The battery impedance test method is: adjust each experimental button cell to 60% SOC, use a current of 1.5C, and a charge and discharge time of 30s to test the DCIR of the battery; the product of the DCIR value of the battery and the 1 / 3C discharge capacity of the battery is used as the characterization of the battery impedance.
[0081] Cycle performance test method: Charge each experimental button cell to 4.95V at room temperature with a constant current and constant voltage of 10mA (0.5C), and the charging cut-off current is 0.5mA (0.02C), and then discharge to 3.0V with a constant current of 10mA (0.5C), record the initial charging capacity and discharge capacity, and calculate the discharge efficiency (%); after repeating the charge and discharge cycle n times, record the discharge capacity of the nth cycle, and calculate the capacity retention rate after cycle (%) = discharge capacity of n cycles / initial discharge capacity × 100%; the cut-off voltage is 4.95V.
[0082] The specific effect data are shown in Tables 1 and 2.
[0083] Table 1
[0084]
[0085]
[0086] Table 2
[0087]
[0088] From Table 1 above, it can be seen that the discharge capacity of the battery prepared in Examples 1 to 6 can reach 128.6 mAh.g -1 , the charging capacity can reach 151.9mAh.g -1 , the discharge efficiency can reach up to 84.7%, which is significantly higher than that of Comparative Example 1, and the DCIR can reach down to 40.3 mΩ, which is significantly lower than that of Comparative Example 1. As can be seen from Table 2, the capacity retention rate of Examples 1-6 is significantly higher than that of Comparative Example 1.
[0089] From the comparison between Example 1 and Comparative Example 1, it can be seen that since Example 1 is different from Comparative Example 1 in that a conductive medium is formed in the carbonized layer, the DCIR of Example 1 is significantly reduced compared with Comparative Example 1, which shows that when other conditions remain unchanged, the interface impedance between the carbonized layer with a conductive medium and the negative electrode sheet is reduced.
[0090] From the comparison between Example 4 and Example 1, it can be seen that the carbon-coated aluminum foil with grooves can increase the interface contact area between the solid electrolyte and the positive electrode sheet, while the interface contact area of the carbon-coated aluminum foil without grooves is smaller, which results in poor first-cycle charge and discharge performance and cycle performance, and increased resistance value. The effect of Example 4 is worse than that of Example 1, but better than Comparative Example 1.
[0091] It can be seen from Example 5 that the length of lithium conductive medium penetrating into the carbonized layer is too short, and the effect is worse than that of Example 1. Compared with Comparative Example 1, although the charging capacity and discharge capacity are similar to those of Comparative Example 1, the internal resistance of the battery is much lower than that of Comparative Example 1.
[0092] It can be seen from Example 6 that when the thermal initiator added is a thermal initiator that does not contain nitrogen, the formed carbonized layer is not doped with nitrogen. The thermal initiator in Example 1 contains nitrogen, so that the formed carbonized layer is doped with nitrogen, which can further improve the interweaving of the carbonized layer and the metallic lithium conductive medium, and further promote the various performance effects of Example 1 to be better than those of Example 6. Although the charging capacity and discharge capacity of Example 6 are similar to those of Comparative Example 1, the internal resistance of the battery is much lower than that of Comparative Example 1.
[0093] It can be seen from Comparative Example 1 that when molten metal lithium is directly dripped on the surface of the cooled solid electrolyte, since the solid electrolyte has completed polymerization and turned into a solid state, the molten metal lithium can no longer melt into the solid electrolyte, resulting in a smaller interface contact area, which in turn makes the first-cycle charge and discharge performance and cycle performance poor, and the resistance value increases.
[0094] It can be seen from Comparative Example 2 that after the lithium conductive medium penetrates into the positive electrode sheet, it is electrically connected to the positive electrode sheet, causing the positive electrode sheet and the negative electrode sheet to short-circuit, resulting in a sudden drop in voltage and causing battery failure.
[0095] In order to further illustrate the beneficial effects of the embodiments of the present invention, distribution curves of different charge and discharge cycle coefficients and capacity retention rates are also made for Embodiment 1, Embodiment 3, Embodiment 4 and Comparative Example 1, as shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the capacity retention rates of Example 1, Example 3 and Example 4 at different charge and discharge cycle coefficients are significantly higher than the capacity retention rate of Comparative Example 1 at different charge and discharge cycle coefficients.
[0096] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A solid-state lithium battery cell, characterized in that: The solid-state lithium battery cell comprises a positive electrode sheet, a solid electrolyte, a carbonized layer and a negative electrode sheet stacked in sequence, a conductive medium is infiltrated into the carbonized layer, the length of the conductive medium in the thickness direction of the carbonized layer is less than the sum of the thickness of the carbonized layer and the thickness of the solid electrolyte, and the conductive medium is connected to the negative electrode sheet; The carbonized layer and the solid electrolyte both contain carbon; the raw material of the carbonized layer before carbonization and the raw material of the solid electrolyte before solidification and polymerization are both solid electrolyte precursors, and the carbonized layer is formed by the surface of the solid electrolyte precursor facing the negative electrode sheet being carbonized by heat; The positive electrode sheet comprises a positive electrode material layer, the positive electrode material layer is also infiltrated with electrolyte branches of the solid electrolyte near the solid electrolyte, and the electrolyte branches are formed by the solid electrolyte precursor infiltrated into the positive electrode material layer through polymerization and solidification; The solid electrolyte precursor is in liquid or semi-solid state, and monomers in the raw materials of the solid electrolyte precursor have not undergone polymerization reaction or have not been completely polymerized.
2. The solid-state lithium battery cell according to claim 1, characterized in that: The negative electrode sheet is a metal lithium sheet, and the conductive medium is metal lithium.
3. The solid-state lithium battery cell according to claim 1, characterized in that: The thickness of the carbonized layer is 5 μm-10 μm.
4. The solid-state lithium battery cell according to claim 3, characterized in that: The length of the conductive medium in the thickness direction of the carbonized layer is 1 μm-10 μm.
5. The solid-state lithium battery cell according to claim 1, characterized in that: The conductivity of the carbonized layer gradually decreases from the direction close to the negative electrode sheet to the direction away from the negative electrode sheet.
6. The solid-state lithium battery cell according to claim 1, characterized in that: The carbonized layer is also doped with nitrogen.
7. The solid-state lithium battery cell according to claim 1, characterized in that: The positive electrode sheet further includes a positive electrode current collector. The positive electrode material layer is arranged on the surface of the positive electrode current collector. The positive electrode material layer includes a spinel positive electrode material.
8. The solid-state lithium battery cell according to claim 7, characterized in that: The portion of the positive electrode material layer close to the solid electrolyte is also infiltrated with solid electrolyte material.
9. A method for preparing a solid-state lithium battery cell, characterized in that: The method for preparing the solid-state lithium battery cell is used to prepare the solid-state lithium battery cell according to any one of claims 1 to 8, and the method for preparing the solid-state lithium battery cell comprises: preparing a positive electrode sheet; placing a solid electrolyte precursor on the positive electrode sheet; A molten conductive medium precursor is coated on the surface of the solid electrolyte precursor away from the positive electrode sheet, the molten conductive medium precursor cools and releases heat so that the surface of the solid electrolyte precursor away from the positive electrode sheet is heated and carbonized to form a carbonized layer, the remaining part of the solid electrolyte precursor is cooled to form a solid electrolyte, at least a part of the molten conductive medium precursor penetrates into the carbonized layer to form a conductive medium, and a negative electrode sheet is formed on the surface of the carbonized layer away from the solid electrolyte.
10. The method for preparing a solid-state lithium battery cell according to claim 9, characterized in that: The conductive medium precursor is metallic lithium; at least a portion of the molten conductive medium precursor infiltrates into the carbonized layer to form a conductive medium, and a negative electrode sheet is formed on a surface of the carbonized layer away from the solid electrolyte, including: Part of the molten metallic lithium is infiltrated into the carbonized layer, and another part of the molten metallic lithium is cooled on the surface of the carbonized layer away from the solid electrolyte to form a metallic lithium layer, and the metallic lithium layer is the negative electrode sheet.
11. The method for preparing a solid-state lithium battery cell according to claim 9, characterized in that: The solid electrolyte precursor includes an olefin monomer, a cross-linking agent, a thermal initiator and a lithium salt, and the mass ratio of the olefin monomer: the cross-linking agent: the thermal initiator: the lithium salt is 100: (0.05-0.25): (0.05-0.25): (8-12).
12. A battery, characterized in that: The battery comprises a shell and a solid-state lithium battery cell as described in any one of claims 1 to 8 located in the shell.
Citation Information
Patent Citations
Composite negative electrode of solid-state lithium battery and preparation method of composite negative electrode
CN108110217A
Solid-state electrolyte-lithium combination body, fabrication method thereof and all-solid-state secondary battery comprising same
CN110767894A